Development and Validation of a Derivative Spectrophotometric Method for Simultaneous Determination of Simvastatin and Ezetimibe - Effat Souri; Masoud Amanlou (E-Journal of Chemistry)
A combination of simvastatin and ezetimibe with complementary mechanisms of action is used for treating high levels of cholesterol in the blood. The aim of this study was to develop a rapid and sensitive derivative spectrophotometric method for analysis of these drugs in combined dosage forms. A first order derivative spectrophotometric method was developed for simultaneous determination of simvastatin and ezetimibe using zero-crossing technique. The measurements were carried out at 219 and 265 nm for simvastatin and ezetimibe respectively. The described method was found to be linear (r2>0.999) over the range of 2-40 μg/mL for simvastatin in the presence of 10 μg/mL ezetimibe at 219 nm and in the range of 1-20 μg/mL of ezetimibe in the presence of 20 μg/mL of simvastatin at 265 nm. The within-day and between-day precision values for both drugs were less than 3% (CV). Also, good recoveries were obtained with both synthetic mixtures and commercial tablets. The proposed method was successfully applied for simultaneous determination of simvastatin and ezetimibe in a pharmaceutical dosage form without any interference from excipients.